What's cooking in Belgium recipes and stories from a food-loving nation - Evans, Neil; Jenkinson, Anna (Luster, 2013)
"Having talked to chefs and farmers, historians and curators up and down Belgium, Anna Jenkinson and Neil Evans have put together a book of recipes and stories that explain Belgium's love affair with food. They travelled from the North Sea coast in the West to the Ardennes forest in the East and learned the secret to making Belgian chips, when the first chocolate praline was made, and how the Spanish, French and Germans have all influenced Belgian cuisine over the centuries."--Provided by publisher.